PENDIDIKAN PANCASILA: NEGARA, AGAMA, DAN WARGA NEGARA - Hutabarat, Dany Try Hutama; Sari, Ajeng Alda; Wella, Anggun; Elfindra, Anzas; Lubis, Firman Febrian; MHD, Faras Musyarih; MPR, Fadillah Asmuni; Rahmadani, Siti (Transpublika Publisher, 2022)
The state is defined as the highest organization among a group of people who have the aspiration to unite, live in the region, and have a sovereign government. The goals of the state, among others, are to expand power, maintain law and order, and achieve general welfare. Of course, in a country there are citizens who take shelter in it. According to the 2006 UUKI, what is meant by a citizen is a citizen of a country that is determined based on statutory regulations. The state is a place for the growth of religion. In the relationship between the state and citizens is very closely related. Citizens play an important role in maintaining the integrity of a country. Muslims in Indonesia must be smart to be a pillar of inter-religious harmony. The plurality of Indonesian citizens in terms of religion, race, ethnicity, and between groups, conflicts often occur which can have an impact on the integrity of the Unitary State of the Republic of Indonesia, abbreviated as NKRI. However, the spirit of maintaining inter-community and ethnic harmony and maintaining the integrity of the Unitary State of the Republic of Indonesia is starting to be forgotten by the successors of this nation. The problem starts with religion or ethnicity.